unc-1: A stomatin homologue controls sensitivity to volatile anesthetics in Caenorhabditis elegans - Rajaram, S. (The National Academy of Sciences, 1998)
To identify sites of action of volatile anesthetics, we are studying genes in a functional pathway that controls sensitivity to volatile anesthetics in the nematode Caenorhabditis elegans. The unc-1 gene occupies a central position in this pathway. Different alleles of unc-1 have unique effects on sensitivity to the different volatile anesthetics. UNC-1 shows extensive homology to human stomatin, an integral membrane protein thought to regulate an associated ion channel. We postulate that UNC-1 has a direct effect on anesthetic sensitivity in C. elegans and may represent a molecular target for volatile anesthetics.